Identification of the amino acid residues and domains in the cysteine‐rich protein of Chinese wheat mosaic virus that are important for RNA silencing suppression and subcellular localization - Sun, Liying (Mol Plant Pathol, 2013)
Cysteine‐rich proteins (CRPs) encoded by some plant viruses in diverse genera function as RNA silencing suppressors. Within the N‐terminal portion of CRPs encoded by furoviruses, there are six conserved cysteine residues and a Cys–Gly–X–X–His motif (Cys, cysteine; Gly, glycine; His, histidine; X, any amino acid residue) with unknown function. The central domains contain coiled‐coil heptad amino acid repeats that usually mediate protein dimerization. Here, we present evidence that the conserved cysteine residues and Cys–Gly–X–X–His motif in the CRP of Chinese wheat mosaic virus (CWMV) are critical for protein stability and silencing suppression activity. Mutation of a leucine residue in the third coiled‐coil heptad impaired CWMV CRP activity for suppression of local silencing, but not for the promotion of cell‐to‐cell movement of Potato virus X (PVX). In planta and in vitro analysis of wild‐type and mutant proteins indicated that the ability of the CRP to self‐interact was correlated with its suppression activity. Deletion of up to 40 amino acids at the C‐terminus did not abolish suppression activity, but disrupted the association of CRP with endoplasmic reticulum (ER), and reduced its activity in the enhancement of PVX symptom severity. Interestingly, a short region in the C‐terminal domain, predicted to form an amphipathic α‐helical structure, was responsible for the association of CWMV CRP with ER. Overall, our results demonstrate that the N‐terminal and central regions are the functional domains for suppression activity, whereas the C‐terminal region primarily functions to target CWMV CRP to the ER.